5-Carboxylcytosine is localized to euchromatic regions in the nuclei of follicular cells in axolotl ovary - Alioui, Anthony; Wheldon, Lee M.; Abakir, Abdulkadir; Ferjentsik, Zoltan; Johnson, Andrew D.; Ruzov, Alexey (Landes Bioscience, 2012)
5-Methylcytosine (5-mC) is an epigenetic modification associated with gene repression. Recent studies demonstrated that 5-mC can be enzymatically oxidised into 5-hydroxymethylcytosine and further into 5-formylcytosine (5-fC) and 5-carboxylcytsine (5-caC). 5-caC has been found in embryonic stem cells and in mouse pre-implantation embryos but no detectable levels of this modification have been reported for somatic tissues to date. Whereas it has been suggested that 5-caC can serve as an intermediate in the process of active demethylation, the function of this form of modified cytosine remains obscure. Here we show that 5-caC is immunochemically detectable in somatic cells of axolotl ovary. We demonstrate that both 5-hmC and 5-caC are localized to the euchromatin in the nuclei of axolotl follicular cells with similar patterns of spatial distribution. Our results suggest that 5-carboxylcytosine may play a distinct functional role in certain biological contexts.